Pedagogical, Interpersonal and Instructional Functions of Code-switching to Support Online Classroom Learning - Ayu Jeanretno Tiara Putri; Sri Wuli Fitriati; Zulfa Sakhiyya (English Education Journal, 2022)
This study was conducted during the COVID-19 pandemic when a shift from traditional classrooms to online classroom learning happened. Faced with online learning challenges, teachers practiced various strategies to support their classes. In EFL contexts, the way teachers manage these challenges can be investigated through online code-switching. The present qualitative study investigates an Indonesian EFL teacher’s perception and use of classroom code-switching in promoting pedagogical, interpersonal, and instructional functions to support teaching and learning in online classroom settings. The study gained data through a semi-structured interview to gauge the EFL teacher’s perception and by observing several online English classroom recordings. The findings were analyzed using Ferguson’s (2003) and Gumperz’s (1982) theories, supported by stimulated recall interviews. The study found that the EFL teacher has a positive and supportive perception of classroom code-switching for online classroom teaching and learning. In realization, analysis results showed that the EFL teacher practiced classroom code-switching in her online classrooms and promoted functions including pedagogical (e.g., reiteration, message qualification, etc.), interpersonal (e.g., establish rapport, negotiate identities), and instructional functions (e.g., negotiate task instruction, disciplining, etc.). The study provided insights on classroom code-switching practice in online settings to encourage teachers to efficiently use code-switching to support their online classroom teaching and learning.